Paramedic survival guide - DiPrima, Peter A., 4 Jr.0 16; 5 (New York : McGraw-Hill Medical, 2012)
The book every paramedic needs to enhance their career and job performance Paramedic Survival Guide offers both novice and experienced paramedics a unique blend of case studies, testimonials, and advice from veterans to help them succeed on their jobs and advance their career. The book also offers advice on how to pick the correct EMT job, the recruitment and interview process, and various career paths and options open to paramedics. Valuable features include Taking it to the Street boxes detailing must-know on-the-job information--Provided by publisher.
Machine generated contents note: 1. History of the EMS Profession (what is EMS?) 2. Your Role in the Health Care System as an EMS provider (different levels of EMT, EMT vs MD, nurse, etc.) 3. Graduation and Credentialing (now you're an EMT!) 4. Career Opportunities (different jobs in EMS military, life-flight, private sector, rural vs urban job settings, etc.) 5. Getting the Job You Want (interviewing, career planning, etc.) 6. Taking the Classroom to the Streets (what is it really like on the job?) 7. Patient Safety: tips from seasoned EMTs 8. EMT Culture (tight-knit community, fast paced job, etc.) 9. One Year Anniversary (feeling comfortable in your role, CME requirements, taking care of yourself - not just patients - so that you don't get burned out) 10. What Next? Paths in your Career as an EMT (educator, MD, etc.) Appendices: Websites, Meetings, Certifying Bodies, Associations, Specialties, CME info, state-by-state regulations.
Includes bibliographical references (p. 139-141) and index.
Keywords: 2 -- 0; 6; Emergency Medical Technicians.;Professional Practice.;Vocational Guidance. -- 20; 20; 2